Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Find the value of n that satisfies 2(n+1)! + 6n! = 3(n+1), where $n! = n\cdot (n-1)\cdot (n-2) \cdots 2\cdot 1$.

Sagot :

Answer:

[tex]n = 5[/tex]

Step-by-step explanation:

Given

[tex]2(n+1)! + 6n! = 3(n+1)![/tex]

Required

Find n

Simplify (n + 1)!

[tex]2(n+1)*n! + 6n! = 3(n+1)*n![/tex]

Factorize

[tex]n![2(n+1) + 6] = 3(n+1)*n![/tex]

Divide both sides by n!

[tex]2(n+1) + 6 = 3(n+1)[/tex]

Open brackets

[tex]2n + 2 + 6 = 3n + 3[/tex]

[tex]2n + 8 = 3n + 3[/tex]

Collect like terms

[tex]2n - 3n = 3 -8[/tex]

[tex]-n =-5[/tex]

Multiply both sides by -1

[tex]n = 5[/tex]

We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.